Small Modular Reactor Control Room Workstation Demonstration. (November 2019) - Stevens, Jessica; LaFerriere, Kevin; Flamand NuScale, Ryan
A control room simulator was designed to model the operation of a NuScale small modular reactor (SMR) nuclear power plant and provide enough fidelity to perform staffing validation studies for Nuscale's Nuclear Regulatory Commission Design Certification Application. The simulator serves as a simulated control room with work stations to mimic the operation of an SMR module, turbine generator, and support systems using a proprietary human system interface (HSI) software package. The simulator, which includes all HSI screens, was designed by a team of Human Factors and Plant Operations staff to capitalize on best practices, lessons learned, and operating experience using the Agile development process. Finally, the design process included the development of plant operating procedures and training material as well as a training platform for future plant operators at an SMR nuclear power plant.